A global analysis of the susceptibility of river basins to invasion of a freshwater zooplankton (Daphnia lumholtzi). (19th December 2020) - Mantovano, Tatiane; Bailly, Dayani; Ferreira, José Hilário Delconte; de Oliveira da Conceição, Eliezer; Cassemiro, Fernanda A. S.; de Campos, Ramiro; Paulo Mormul, Roger; Rangel, Thiago Fernando; Lansac‐Tôha, Fábio Amodêo
Abstract: Climate change and species invasions pose serious threats to biodiversity. Daphnia lumholtzi Sars, 1885, a cladoceran species native to Africa, Asia, and Oceania, has successfully invaded large sections of North and South America, there is evidence that the increase in the Earth's temperature and the number of reservoirs have facilitated this process. In this context, our study evaluated the effects of climate change on the invasive potential of D. lumholtzi, identifying the environmental suitability of non‐native river basins around the world to invasion by this species. Using ecological niche modelling, we predicted potential distribution areas of D. lumholtzi in non‐native continents at the present time, in 2050 and 2080. For future scenarios we considered two hypotheses of greenhouse gas emission: extreme (8.5 representative concentration pathways) and moderate (4.5 representative concentration pathways). We used different algorithms in niche models within the ensemble forecast approach to estimate the potential distribution of D. lumholtzi river basins worldwide. Furthermore, we developed a susceptibility index, that uses the presence of D. lumholtzi, its suitability information, area, and number of reservoirs to evaluate the susceptibility to invasion for each river basin. Our predictions showed that future climate change will have a strong influence on the invasive potential of D. lumholzti, potentially expanding its distribution in eastern North America and boosting invasion across Europe, especially at the end of the century. The susceptibility index also showed that many river basins that presently are not vulnerable to invasion by this species will become susceptible to invasion, these basins lie mainly in Europe. Our results will be useful for monitoring and mitigating the spread of this species, especially for river basins identified as highly susceptible to invasion. Thus, we suggested that D. lumholtzi should be a high priority for monitoring and preventive actions against invasion of these river basins. We also suggest that better risk assessments, that include invasive species and reservoirs, should be a priority in national energy development plans.